The study of the validity and reliability of the Occupational Self-Assessment-traditional Chinese version. Issue 1 (June 2020) - Pan, Ay-Woan; Chung, LyInn; Chen, Tsyr-Jang; Hsiung, Ping-Chuan
Introduction: Health professionals who work in mental healthcare settings need to use standardised, objective instruments; however, it is also extremely important that they maintain a client-focused perspective. The purpose of this study was to investigate the validity and reliability of the 'Traditional Chinese version of the Occupational Self-Assessment' (TC-OSA). Methods: A total of 593 participants with mental illnesses participated in the study. The data were analysed using confirmatory factor analysis as well as the Rasch measurement model. Results: The results of our analysis revealed that the TC-OSA encompasses four domains: self-performance (11 items), self-habituation (5 items), self-volition (5 items) and environment (8 items). Most of the items within each domain were found to have a good fit with the Rasch measurement model, whereas the CFA index was found to have a good fit for only three of the domains, the one exception being the environment domain. Conclusions: We suggest applying the scale in clinical practice to identify the priority of intervention and as a measure for changes in outcomes. Further development and refinement of the environmental domain is guaranteed.